2008
DOI: 10.1021/jo702456k
|View full text |Cite
|
Sign up to set email alerts
|

Local Polarity in CO2-Expanded Acetonitrile: A Nucleophilic Substitution Reaction and Solvatochromic Probes

Abstract: Many processes that use highly tunable gas-expanded liquids (GXLs) rely on the fact that CO2 addition can greatly affect the polarity of the solvent. We have examined several measures of bulk and local polarity in CO2-expanded acetonitrile to enable more effective exploitation of these polarity changes. The rate of the nucleophilic substitution reaction of tributylamine with methyl p-nitrobenzenesulfonate has been analyzed as a function of solvent composition by using in situ high-pressure UV/vis spectroscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…This scenario is expected to decrease the solvent polarity, which in turn may enhance the homogenisation of the reaction. [19] The conversion of propargyl alcohol was substantially boosted using 50 bar CO 2 and either FatPhos1'/AgOC 10 (98 %, entry 10) or FatPhos2 (92 %, entry 11). In comparison, the pure FatPhos1 ligand gave only 59 % conversion and poor selectivity of 85 % towards the desired product (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…This scenario is expected to decrease the solvent polarity, which in turn may enhance the homogenisation of the reaction. [19] The conversion of propargyl alcohol was substantially boosted using 50 bar CO 2 and either FatPhos1'/AgOC 10 (98 %, entry 10) or FatPhos2 (92 %, entry 11). In comparison, the pure FatPhos1 ligand gave only 59 % conversion and poor selectivity of 85 % towards the desired product (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…the amount of antisolvent gas added to the organic. Ford et al [ 14 ] reported the Kamlet-Taft solvatochromic parameters for CO 2 -expanded acetonitrile. The polarity/polarizability (π*) of the CO 2 -expanded acetonitrile was measured as a function of added CO 2 in the mixture, as shown in Figure 1 .…”
Section: Tunable Solventsmentioning
confidence: 99%
“… Kamlet-Taft dipolarity and polarizability (π*) of acetonitrile/CO 2 mixture as a function of CO 2 mole fraction [ 14 ]. …”
Section: Tunable Solventsmentioning
confidence: 99%
“…Most importantly, the physical properties of SC CO 2 can be adjusted by the pressure and temperature continuously. [5] Furthermore, CO 2 can be easily recaptured and recycled after utilization. ILs are an interesting class of tunable and designable solvents with essentially zero volatility, wide electrochemical window, nonflammability, high thermal stability, and wide liquid range.…”
mentioning
confidence: 99%